2005
DOI: 10.1111/j.1365-2516.2005.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between patients’, physicians’ and pharmacists’ preferences for treatment products in haemophilia: a discrete choice experiment

Abstract: The provision of health care to patients with haemophilia through replacement of the deficient coagulation factor is the result of a complex interaction between patients, physicians and policy makers, each carrying their individual sets of preferences. Preferences of patients, physicians and pharmacists towards perceived viral safety, risk of inhibitor development, infusion frequency during prophylaxis, pharmaceutical dosage form, distribution modes and price were evaluated by conjoint analysis, using a discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 37 publications
7
66
0
Order By: Relevance
“…Choice-format conjoint surveys often include attributes that describe disease outcomes and treatment attributes as certain outcomes. [30][31][32][33] Rarely do studies describe attributes in probabilistic terms. Understanding and conceptualizing numerical probabilities is often cognitively challenging.…”
Section: Discussionmentioning
confidence: 98%
“…Choice-format conjoint surveys often include attributes that describe disease outcomes and treatment attributes as certain outcomes. [30][31][32][33] Rarely do studies describe attributes in probabilistic terms. Understanding and conceptualizing numerical probabilities is often cognitively challenging.…”
Section: Discussionmentioning
confidence: 98%
“…Several DCE studies have shown that patients and physicians may differ substantially in their trade-offs between health-care interventions (Bishop et al , 2004; Lee et al , 2005; Mantovani et al , 2005; de Bekker-Grob et al , 2009). By understanding factors that influence patients' treatment decisions, physicians may become more sensitive to individual patients' preferences/concerns, which may have a positive effect on the process and outcomes of shared decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the useable response rate was 16.3 per cent (161 out of 985). The sample size is comparable with other marketing or health care DCEs (Arora, 2006;Mantovani et al, 2005;Ryan and Farrar, 2000) and exceeds other discrete choice or conjoint-based experiments (Dean, 2004;Haas, 2005;Johnson and Backhouse, 2006;King et al, 2007;Koo et al, 1999;Lancsar et al, 2007;Tappenden et al, 2007).…”
Section: Insights Into Public Preferencesmentioning
confidence: 95%